Washington Street near the Old South Meeting House, April 11, 1922 - Belcher, Arnold L. (Tufts Archival Research Center, 2005)
Elevated view east-southeast of the area surrounding the Old South Meeting House, located at 310 Washington Street. The Old South Building, located at 294 Washington Street, is visible behind and to the left of the Old South Meeting House. Buildings lining the west side of Washington Street are included in the lower-half of the photograph. 9 1/2 x 7 5/8 Photographs